Simulation of a Permittivity Measurement System with Microstrip Structure at ISM Frequency Incorporate with Lookup Table - Chokenukul, Paween; Worasawate, Denchai (Engineering and Technology Horizons, 2023)
This research aims to simulate a permittivity measurement system utilizing a microstrip structure with sonnet software to bring the discovered knowledge to develop the permittivity measurement instrument that has high efficiency and low cost in the next. This research has designed and simulated microstrip structure at ISM frequencies of 13, 27, and 40 MHz, for permittivity values of 35, 55, and 75 are used, also loss tangent values of 0.2, 0.4, and 0.6 are used, and conduct the simulation measurement system for creating a lookup table size of 11x11, 5x5, and 3x3 respectively. Then, bring the results from the simulation to calculate to find the permittivity values and loss tangent values. After, find the error values. The research results found that directly calculating permittivity and loss tangent from S-parameters results in significantly high percentage errors. Therefore, the researcher will propose a method to find values from a lookup table. The results obtained from the proposed method exhibit consistency with the actual permittivity through errors that are below 0.1984 percent. Thus, the simulations of the measurement system in this research can apply to find permittivity values and loss tangent values of material having unknown values. Moreover, it is still able to develop into an actual measuring device that possesses both efficiency and worth in the future.